A systems approach to a spatio-temporal understanding of the drought stress response in maize - Zhenyan Miao (Nature Portfolio, 2017)
Abstract Crops are often subjected to periods of drought stress during their life cycle. However, how stress response mechanisms contribute to the crosstalk between stress signaling pathways and developmental signaling pathways is still unknown. We built a gene co-expression network from a spatio-temporal transcriptomic map of the drought stress response in maize (Zea mays), profiled from three tissues and four developmental stages and characterized hub genes associated with duplication events, selection, and regulatory networks. Co-expression analysis grouped drought-response genes into ten modules, covering 844 highly connected genes (hub genes). Of these, 15.4% hub genes had diverged by whole-genome duplication events and 2.5% might then have been selected during natural domestication and artificial improvement processes, successively. We identified key transcription factor hubs in a transcriptional regulatory network, which may function as a crosstalk mechanism between drought stress and developmental signalling pathways in maize. Understanding the evolutionary biases that have evolved to enhance drought adaptation lays the foundation for further dissection of crosstalk between stress signalling pathways and developmental signalling pathways in maize, towards molecular design of new cultivars with desirable yield and greater stress tolerance.